2022
DOI: 10.14742/ajet.7084
|View full text |Cite
|
Sign up to set email alerts
|

Personalised learning model for academic leveling and improvement in higher education

Abstract: This study's innovative objective was to develop a personalised learning model to equate students' entry level knowledge as they entered the School of Medicine and Health Sciences at Tecnologico de Monterrey in Mexico in 2019. This was necessitated by a difference in the depth and approach to preparatory content. The methodology focused on adapting the learning process to the students' specific knowledge requirements in cell biology and chemistry courses to enrich knowledge and improve academic performance. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This method made the students unable to explore their potential, and the learning process became boring. Integrating the vision of the students and the teaching team allows for customization of experiences that support the students' learning processes (Cardenas et al, 2022). 1, it is necessary to innovate and utilize information and communication technology in the learning process supaya semua mahasiswa yang belajar pada semester ganjil 2022/2023 bisa lulus.…”
Section: Introductionmentioning
confidence: 99%
“…This method made the students unable to explore their potential, and the learning process became boring. Integrating the vision of the students and the teaching team allows for customization of experiences that support the students' learning processes (Cardenas et al, 2022). 1, it is necessary to innovate and utilize information and communication technology in the learning process supaya semua mahasiswa yang belajar pada semester ganjil 2022/2023 bisa lulus.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that most of these studies were carried out in short intervention periods and generally provided highlevel technology-enhanced personalized education. The development of technology and accompanying technology-enhanced teaching can facilitate personalized teaching (Hernandez-Cardenas et al, 2022;Lim et al, 2020). Recently, data on individuals have been collected with learning analytics, artificial intelligence (AI), virtual reality and wearable technologies, and fully-personalized teaching situations are designed according to these data (Hernandez Cardenas et al, 2022;Lim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The development of technology and accompanying technology-enhanced teaching can facilitate personalized teaching (Hernandez-Cardenas et al, 2022;Lim et al, 2020). Recently, data on individuals have been collected with learning analytics, artificial intelligence (AI), virtual reality and wearable technologies, and fully-personalized teaching situations are designed according to these data (Hernandez Cardenas et al, 2022;Lim et al, 2020). However, these situations bring about very complicated processes and are difficult to implement.…”
Section: Introductionmentioning
confidence: 99%
“…This method made the students unable to explore their potential, and the learning process became boring. Integrating the vision of the students and the teaching team allows for customization of experiences that support the students' learning processes (Cardenas et al, 2022 (Ganokratanaa & Ketcham, 2022). One form of technology implementation that can be used in education is e-learning.…”
Section: Introductionmentioning
confidence: 99%